Implementasi Metode Diskusi Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) Kelas X MAN 5 Kediri - Iqlima Zahari (FKIP, Universitas Palangka Raya, 2022)
The term implementation is usually associated with an activity, which is carried out to achieve certain goals. Discussion is a group activity of a group of students, talking to each other, exchanging information and opinions about a topic or problem, where each child wants to find answers / solutions to problems from all existing aspects and possibilities. Learning motivation is